Pelatihan Pidato Bahasa Jawa untuk Memperkuat Literasi Bahasa Daerah di Desa Sriwedari Kabupaten Magelang - Ndaru Prasetyo Aji; Lesa Paranti; Erviyandani Erviyandani; Septiana Nugrahani; Supriyati Supriyati (Riau Journal of Empowerment, 2023)
Javanese is a language that is widely spoken in addition to other regional languages, including in Sriwedari Village Salaman District Magelang Regency Central Java. The use of Javanese among the people of Sriwedari Village, especially the younger generation, has a problem, namely the low level of Javanese literacy. This is based on observations in each hamlet in Sriwedari Village stating that young people in Sriwedari Village do not understand more deeply about Javanese and Javanese speech, while in community activities using Javanese. Therefore, there is a need for Javanese speech training in Sriwedari Village. The purpose of this service is to improve Javanese literacy skills, especially in terms of speaking so that it is expected to foster a sense of love for the nation's culture. The method used in this training begins with lectures, demonstrations, questions and answers, and evaluation. The result of the service program is to produce the next generation of the nation who can preserve the Javanese language through Javanese speech.